Hubungan Konsep Diri dan Kecemasan dengan Pengambilan Keputusan untuk Berobat ke Dokter Spesialis (Penelitian pada Pemanfaatan Program JPK PT. Jamsostek (Persero) Bandung I) - Suprayogi, M. Nanang; Firsty, Dyah Ayu (Humaniora, 2012)
This study aims to examine the relationship between self-concept and anxieties of the JPK PT. Jamsostek (Persero) participants who were ill with the decision to take advantage of the handling of the specialist physician. The measurement of self-concept used in this study is compiled based on the dimensions of self-concept developed by Fits, consisting of self-identity, self-behavioral, and self-judging. The measurement of anxiety refers to Mc Neil, et al, consisting of cognitive components, physiological responses, and behavior. The measurement of the decision-making refers to Hunsaker, et al, consisting of information complexity and level of focus. The study was conducted on 109 JPK participants treated at the hospital in the working area of PT. Jamsostek (Bandung I) with incidental purposive sampling technique. From the statistic test can be seen that there is a relationship between self-concept and decision making for treatment to a specialist. There is a relationship between anxieties with making the decision to go to a specialist. There is a relationship between self-concept and anxieties, together with the decision making to go to a specialist.